PENGEMBANGAN BUKU AJAR FITOREMEDIASI UNTUK MATAKULIAH PENCEMARAN LINGKUNGAN - Haslinda Yasti Agustin (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2017)
The purpose of this study is to produce products such as phytoremediation handbook for the course of Environmental Pollution. This study uses a model of research and development Borg & Gall until the fifth stage is a major product revision. Data obtained from the handbook development expert validation sheet material, teaching materials experts, education professionals (lecturers), and students, who then all the data is analyzed. The results of the validation calculation shows the results valid and sufficient valid and does not need revision, but the revision is still being done by taking into account suggestions and comments provided by all validator to fix the product. Results of the study are the product of the handbook entitled "Phytoremediation (Efforts to Maintain Quality Water Environment)" which has advantages such as: easy to understand language and accompanied by images that support, each chapter comes with questions related to environmental issues that can be fishing mindset of students to be more concerned about the environment and find solutions to problems, an explanation of phytoremediation, application and impact of the plant is described in full, while the drawback is still keeping up the real issues waters in Indonesia, tools and materials for research must be clearly stated so the procedure can work well understood, as well as the need for a glossary to explain terms of biology that are important. Keywords: phytoremediation, handbook, environmental pollution